The currents on the south-eastern coasts of Newfoundland, and the amount of indraught into the larger bays on the south coast [electronic resource] : from investigations of the tidal and current survey in the season of 1903 - Dawson, W. Bell (William Bell), 1854-1944.; Canada. Dept. of Marine and Fisheries. (Ottawa : Govt. Print. Bureau, 1906)
Tables. "Reprinted, 1906." "Published by the Department of Marine and Fisheries ." Electronic reproduction. Mode of access: Internet. 44